Formulation of dispersed gliclazide powder in polyethylene glycol–polyvinyl caprolactam– polyvinyl acetate grafted copolymer carrier for capsulation and improved dissolution - Ahmed Mahdi Dukhan, Ather; Mohamad Yusoff, Nursazreen Amalina; Kyaw Oo, May; Sengupta, Pinaki; Doolaanea, Abd Almonem; Aljapairai, Khater Ahmed Saeed; Chatterjee, Bappaditya (Association of Pharmaceutical Teachers of India, 2018)
Background: Oral bioavailability of gliclazide, a hypoglycemic drug, is hindered by its low aqueous solubility. Improvement of solubility will enhance dissolution rate and in turn the bioavailability. This research aimed to formulate the solid dispersed gliclazide using a novel polyethylene glycol–polyvinyl caprolactam–polyvinyl acetate grafted copolymer (Soluplus®) as carrier to enhance in-vitro dissolution and to study drug-carrier physical interaction. Method: Final solid dispersion (SDGLC) containing drug:carrier (1:8 w/w) was prepared by solvent evaporation after drug-polymer miscibility study. The SDGLC powder was characterized by differential scanning calorimetry (DSC), attenuated total reflectance infra-red spectroscopy (ATR-IR), powder X-ray diffraction (PXRD), and scanning electron microscopy (SEM). SDGLC powder was filled in gelatin capsule after flowability and moisture analysis followed by assay, disintegration and in-vitro dissolution study. Results: Miscibility study showed negative values of free energy transfer indicating spontaneous solubilization of drug with increase in carrier concentration. Absence of sharp melting peak in SDGLC was observed by DSC. Reduced peak intensity at specific 2θ values in PXRD indicates loss of crystallinity in solid dispersion. Interaction to form H-bond between gliclazide and Soluplus® was evidenced by ATR-IR. SDGLC filled capsule resulted in 20% improved dissolution (approximately 20% higher) in 0.1(N) HCl and phosphate buffer pH 7.4 compared to physical mixture (gliclazide-Soluplus®) containing capsule. Conclusion: Soluplus® effectively enhanced gliclazide solubility in solid dispersed state and SDGLC powder filled capsules could provide pH independent and improved in-vitro dissolution for gliclazide.